Evaluation of Lightning Protection and Grounding System in a Hazardous Zone 2 Oil and Gas Facility Based Based on Field Testing and WinIGS Modeling - Erwin Elysar; Iwa Garniwa (Politeknik Siber Cerdika Internasional, 2026)
Background: Oil and gas facilities operating in Hazardous Zone 2 require reliable lightning protection, grounding, bonding, and surge protection systems to ensure electrical safety, protect personnel and equipment, and maintain operational continuity under potential flammable conditions. Objective: This study aims to evaluate the overall performance of the lightning protection and grounding systems in a Hazardous Zone 2 oil and gas facility based on field testing, technical assessment, and grounding system modeling. Methods: The research methods consisted of soil resistivity measurement using the Wenner four-point method, grounding resistance testing using the fall-of-potential method, continuity testing of grounding and bonding connections using the four-wire Kelvin method, lightning risk assessment based on IEC 62305-2024, evaluation of the existing lightning protection layout using the rolling sphere method, and grounding system verification using WinIGS software based on IEEE Std 80. Field testing was conducted on grounding rods, grounding rings, busbars, air terminals, down conductors, grounding cables, control panels, and other bonding components within the oil and gas facility. Results: The measurement results showed that the average combined soil resistivity value was 4.98 Ω·m with a two-layer soil model. The results of the grounding resistance test showed that most of the grounding points still met the ideal limits with a value range of 0.410 Ω to 1.580 Ω. However, one grounding point was found to be in a rejected condition and required repair. Conclusion: This study demonstrates that evaluating grounding and lightning protection systems in hazardous areas requires an integrated approach, considering grounding resistance, soil resistivity, bonding continuity, physical grounding conditions, lightning protection, and grounding system simulations.